Integrated Molecular and Morphological Studies of the Daucus guttatus Complex (Apiaceae) - Arbizu Berrocal, Carlos Irvin (2016)
In a previous study using 94 nuclear orthologs, we reported the species status of the Daucus guttatus complex to be unresolved, partitioned into three clades. In the present study, a subset of ten of these 94 orthologs was used to infer the phylogeny of the D. guttatus complex and related species. A near parallel set of accessions, planted in a common garden, was used for morphological analyses. The molecular trees are highly resolved for most of the clades, grouping accessions of the D. guttatus complex into four clades. Bayesian concordance analysis and a coalescent approach gave slightly different topologies. Morphological data likewise support four taxa in the complex. Moreover, herbarium research from a companion study informs nomenclature for taxa of the complex. We identify these four clades as D. bicolor, D. conchitae, D. guttatus, and D. setulosus; internested in or among these segregates are the phenetically distinctive species D. glochidiatus, D. involucratus, D. littoralis, and D. pusillus. Our research redefines species variation in the D. guttatus complex, clarifies species names, interspecific relationships, confirms a useful subset of nuclear orthologs for studies of dominant topologies of Daucus, and discovers morphological characters allowing proper identification of the four species of the D. guttatus complex and related species.